Fetal biometry in the Korean population: reference charts and comparison with charts from other populations. (21st May 2014) - Kwon, Ji Young; Park, In Yang; Wie, Jeoung Ha; Choe, Suyearn; Kim, Chan Joo; Shin, Jong Chul
ABSTRACT Objective The objectives of this article were to construct size charts for fetal biometry in the Korean population and to identify ethnic differences in fetal biometry. Method A prospective, cross‐sectional study was performed with 986 fetuses between 15 to 40 weeks of gestation. The following biometric variables were measured: biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), and long bones lengths including the femur, tibia, humerus, and ulna. For each measurement, regression models were fitted to estimate the mean and standard deviation at each gestational age. The calculated centiles were compared with centiles from other populations using Z‐scores. Results New charts for the Korean population were presented for the fetal biometric variables. Most of the parameters were similar to those for the Italian population. Also, in comparison with the North American and UK populations, Korean fetuses had greater BPD, HC, and AC in the first half of pregnancy but tended to measure progressively smaller with advancing gestational age. In comparison with the Hong Kong population, Korean fetuses had a longer femur length at any gestational age. Conclusion We present size charts for fetal biometry for the Korean population using the recommended methodology, suggesting they are different from what is reported in other ethnicities. © 2014 John Wiley & Sons, Ltd.